The Law of Arbitration Rules that are Final and Binding - Sugiyono, Heru; Suyanto, Heru; Agustanti, Rosalia Dika (UI Scholars Hub, 2020)
A request in a district court for annulment of an arbitration, or arbitral, award is a form of legal remedy that claims dissatisfaction with the award by one or more parties. It contravenes the provisions that stipulate the finality of the award and its permanently binding legal force. The attempt to invalidate the arbitral award seems to reflect the party’s (or parties’) disobedience to it. The research method here employed normative juridical review of various library materials consisting of primary legal sources from related laws and regulations, secondary materials which formed the explanations used in the analysis of the primary legal materials in the form of doctrine, academic views, judicial decisions, document searches, books, and scientific works. The legal material is identified and analyzed to achieve the objectives of the study. The results indicate that there is legal uncertainty related to the provision, specifically whether a district court can overturn a final arbitration award and that it carries the legal force to bind the parties. Therefore, it is necessary to create that certainty, and write off Law No. 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, article 70. Arbitrators are encouraged to act more professionally in examining and delivering fair arbitration awards without being tainted by false evidence or gimmicks.